2015
DOI: 10.1038/ncomms7294
|View full text |Cite
|
Sign up to set email alerts
|

Edge dislocation slows down oxide ion diffusion in doped CeO2 by segregation of charged defects

Abstract: Strained oxide thin films are of interest for accelerating oxide ion conduction in electrochemical devices. Although the effect of elastic strain has been uncovered theoretically, the effect of dislocations on the diffusion kinetics in such strained oxides is yet unclear. Here we investigate a 1/2o1104{100} edge dislocation by performing atomistic simulations in 4-12% doped CeO 2 as a model fast ion conductor. At equilibrium, depending on the size of the dopant, trivalent cations and oxygen vacancies are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
143
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(163 citation statements)
references
References 73 publications
16
143
4
Order By: Relevance
“…Using hybrid Monte Carlo and MD simulations, Sun et al 133 also made similar observations on an edge dislocation in doped and pure CeO 2 . They found that segregated dopants at the dislocation act as strong blocks to free movement of oxygen vacancies, and the dopantvacancy interaction prevails.…”
Section: Misfit Dislocationssupporting
confidence: 53%
See 1 more Smart Citation
“…Using hybrid Monte Carlo and MD simulations, Sun et al 133 also made similar observations on an edge dislocation in doped and pure CeO 2 . They found that segregated dopants at the dislocation act as strong blocks to free movement of oxygen vacancies, and the dopantvacancy interaction prevails.…”
Section: Misfit Dislocationssupporting
confidence: 53%
“…Surprisingly, in all four dislocations, they observed enhancement in oxygen diffusivity, and the activation energies were significantly lower than those in the bulk. While these are interesting observations in contrast to others, Sun et al 133 pointed out that the high diffusivity observed in UO 2 could be largely due to the interstitial oxygen diffusion, in contrast to the vacancy diffusion considered in their study. While these studies have opened up this area of research particularly in setting up the methodologies to perform such simulations, at this point, it is quite obvious that there simply aren't enough studies to fully elucidate dislocation effect on oxygen diffusion, and conclusions from these few results should be drawn with care.…”
Section: Misfit Dislocationscontrasting
confidence: 52%
“…These are known to hinder oxygen ionic transport. 86,87 On the other hand, in VAN films comprising ionically conducting SDC nanopillars, the crystallinity of the SDC phase is much enhanced. 50,56 The reason for the enhanced crystallinity in VAN films is related to the large area vertical heteroepitaxy along many interfaces, 73 contrasting with the single interface formed in a planar film.…”
Section: B Improved Crystallinity Of Ionic Conductorsmentioning
confidence: 99%
“…13 Conductivity maxima at x = 0.1 have also been observed by Shing et al 14 There has been somewhat less attention paid computationally to Ce1-xCaxO2-x than its rareearth analogues. Calculations in the dilute limit and in the static limit (T = 0 K and neglecting all vibrations) suggest a preference for the divalent dopant and oxygen vacancy to be located Using a similar hybrid Monte Carlo approach to that in our previous work 4 , Sun et al 24 have shown that in rare-earth doped CeO2 oxide ion diffusion is slower at edge dislocations because of the enrichment in rare-earth and depletion in mobile oxygen vacancies at these dislocations. By analogy with behaviour in metals, it had been suggested that dislocations also enhance ionic conductivity, but the reverse is observed in the simulations of Sun et al 24 In this paper we also make a preliminary study of the ÎŁ5(310) grain boundary in Ce1-xGdxO2-x/2 (x = 0.2) to examine if the same conclusion applies at a different type of interface.…”
Section: +mentioning
confidence: 99%
“…The resulting conductivity is 0.016 S cm -1 which is about the same as the bulk MCR value and less than that for a random distribution of cations. Sun et al 36 have shown that in rare-earth doped CeO2 oxide ion diffusion is slower at edge dislocations because of the enrichment in rare-earth and depletion in oxygen mobility. Seeing no marked conductivity enhancement, our results are broadly similar to these results -in general there will be a play-off between the rare-earth enrichment and a possible reduction in activation energies for migration mechanisms at interfaces, as is observed in metals and at the {001} surface of alkaline earth oxides.…”
Section: Grain Boundarymentioning
confidence: 99%